THE STRATEGIC ROLE OF SERVICE QUALITY IN SHAPING GENERATION Z’S PURCHASE DECISIONS - lati sari dewi; Siti Amirah Makarim (LP2M Universitas Perjuangan Tasikmalaya, 2026)
This study aims to examine the effect of service quality on Generation Z’s purchase decisions at Hidmat Mart Suryalaya, Tasikmalaya. The research employed a quantitative descriptive approach. The population consisted of all consumers of Hidmat Mart Suryalaya Tasikmalaya, with a sample of 96 respondents selected using the accidental sampling technique. Data were collected through questionnaire distribution and analyzed using simple linear regression.The statistical analysis results indicate that the service quality variable obtained a t-value of 3.890, which is greater than the t-table value of 1.661 at a 5% significance level (α = 0.05) with 94 degrees of freedom. Additionally, the significance value of 0.001, which is lower than 0.05, confirms that the alternative hypothesis is accepted and the null hypothesis is rejected. These findings demonstrate that service quality has a significant effect on Generation Z’s purchase decisions, contributing 13.9% to the variation in purchase decisions, while the remaining percentage is influenced by other factors outside this studyq